Between the Library and Lectures: How Can Nature Be Integrated Into University Infrastructure to Improve Students’ Mental Health - Boyd, Francesca (Frontiers in Psychology, 2022)
The university campus provides the backdrop to a student’s education and social journey. For many students, the transition from secondary school through to graduation can be one of upheaval, geographical, financial and social change. Evidence suggests increasing levels of mental health difficulties amongst UK university students. The university campus is a possible resource to mitigate wellbeing issues through facilitating the salutogenic effects of engagement with nature. This mixed method research examines the opportunity to integrate nature through interventions for University of Sheffield undergraduate students. It uses a green prescription style activity and a specially designed mobile phone app. Through focus groups the participants’ experience reveals the necessity for a whole university approach that considers intervention and campus design simultaneously. This study’s findings qualify research into young adult’s experience of urban green spaces and their tangible connection to plants such as trees. Policy and practice implications include the requirement for a coherent approach to understanding the place-attachment aspects to nature in the university environment. Further afield, there is a need for collaborative wellbeing interventions and urban green space development within the UK context.